PREFERENCE IN SENIOR HIGH SCHOOL STRAND: A DESCRIPTIVE STUDY - Anelfa E. Badilla; Elizabeth D. Dioso, Ed. D (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Deciding on what strand to take in senior high school is important for it is the beginning of their chosen line of work in the future. This descriptive study was to determine the influence of preference of a Senior High School strand that is commonly encountered by the senior high school students in terms of personal interest, family influence, peer influence, financial condition, and employability. Using an adapted questionnaire it was found out that personal interest was the most influencing factor in choosing a strand of senior high school students of New Bataan National High School; Camanlangan National High School; and San Miguel National High School. Personal interest play an important role in choosing a course to study, however other factors should be consider such as job prospects, job demands, academic prerequisites, and personal circumstances. There should be a regular school career guidance program where the senior high school tracks, strands and specializations are properly discussed so that students can really decide and take the right strand which is in line with their future work or career.